2019
DOI: 10.1038/s41416-019-0427-4
|View full text |Cite
|
Sign up to set email alerts
|

Exome and immune cell score analyses reveal great variation within synchronous primary colorectal cancers

Abstract: BACKGROUND: Approximately 4% of colorectal cancer (CRC) patients have at least two simultaneous cancers in the colon. Due to the shared environment, these synchronous CRCs (SCRCs) provide a unique setting to study colorectal carcinogenesis. Understanding whether these tumours are genetically similar or distinct is essential when designing therapeutic approaches. METHODS: We performed exome sequencing of 47 primary cancers and corresponding normal samples from 23 patients. Additionally, we carried out a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…In patient C, this shared mutation could either suggest a common tumour origin or is a striking example of convergent evolution in tumour development, likely arising via the serrated BRAF pathway from sessile serrated polyp precursors. However, overall our results suggest syCRCs have a tendency to originate independently, while often accessing the same mutational processes 29,30,32 . In terms of the temporal development of the tumours, for the older patients B (79 years of age) and C (70 years of age) there are no records of prior endoscopy or biopsies prior to the index admission.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In patient C, this shared mutation could either suggest a common tumour origin or is a striking example of convergent evolution in tumour development, likely arising via the serrated BRAF pathway from sessile serrated polyp precursors. However, overall our results suggest syCRCs have a tendency to originate independently, while often accessing the same mutational processes 29,30,32 . In terms of the temporal development of the tumours, for the older patients B (79 years of age) and C (70 years of age) there are no records of prior endoscopy or biopsies prior to the index admission.…”
Section: Discussionmentioning
confidence: 61%
“…Analysis of the microbiome associated with each tumour in patient A revealed reduced diversity of the gut microbiota, which could be reflective of a dysbiosis related to the patient's history of ulcerative colitis 34 , although these results could have been influenced by the administration of an antibiotic bowel preparation in this case. A previous study has shown differences in immune cell scoring between synchronous tumour pairs 29 . Immune score quantification has been validated as a prognostic marker of risk of recurrence in colon cancer, with the quality and density of the immune infiltrate affected by factors including the pre-existing tumour microenvironment, the tumour genetics and the gut microbiome 35 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…sCRC has been associated with FAP, ulcerative colitis, and hyperplastic polyposis; however, these were only present in 10 % of sCRC cases(Lam et al, 2011). Recently, molecular analysis of 47 tumours in 23 patients revealed a different mutation status in simultaneous lesions, as most tumour pairs did not show similar changes in genes, indicating heterogeneity of tumours that could complicate the treatment choice(Hänninen et al, 2019). The authors also evaluated Immunoscore differences in sCRC: Only 16% of synchronous tumours had an equal Immunoscore, and the overall immune response was more significant in MSI tumours(Hänninen et al, 2019).…”
mentioning
confidence: 99%
“…Recently, molecular analysis of 47 tumours in 23 patients revealed a different mutation status in simultaneous lesions, as most tumour pairs did not show similar changes in genes, indicating heterogeneity of tumours that could complicate the treatment choice(Hänninen et al, 2019). The authors also evaluated Immunoscore differences in sCRC: Only 16% of synchronous tumours had an equal Immunoscore, and the overall immune response was more significant in MSI tumours(Hänninen et al, 2019). These results indicate that multiple factors are involved in the development of sCRC, and this could be future research path in the current study group and in Latvia in general.In the current study, 155/553 cases (28 %) presented synchronous adenomas.…”
mentioning
confidence: 99%